Unpacking the Advantages and Disadvantages of Blended Learning in Masters Education Management - A Qualitative Case Study - Haryanto, Sigit; Sumayah, S; Kurniawan, Fitri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This qualitative case study investigates the advantages and disadvantages of blended learning in Magister Education Management with a focus on students and teachers' perspectives. Methodology: The study took a qualitative approach, with data gathered through in-depth interviews, observations, and documentation analysis. Results: The findings highlight the benefits of blended learning, such as flexibility, access to a variety of materials, and enhanced productivity and engagement. However, the study also identified flaws such as technical issues, a lack of face-to-face engagement, and a digital divide. Applications/Originality/Value: The study's findings add to the corpus of research on blended learning in Masters Education by offering significant insight into efficient implementation. The study is significant because it informs the creation of successful blended learning methodologies that boost students' outcomes and instructor experiences increasing the quality of education in Magister.